2018
DOI: 10.2478/humo-2014-0003
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of VO<sub>2</sub>max based on age, body mass, and resting heart rate

Abstract: Purpose. The aim of the present study was to develop a non-exercise regression model for predicting maximal oxygen uptake (VO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 7 publications
0
11
0
1
Order By: Relevance
“…These findings present new research opportunities, as the power at VLF is related to changes in the humoral system 27 , while DFA fluctuations have been considered useful when analyzing the intrinsic behavior of a system 28 . Finally, the age of the participants influenced the final prediction model of VO 2max , with correlations of r = 0.423 in men and r = 0.212 in women, which has been considered in the development of other prediction models 29 . The Durbin Watson test for independence of variables showed, in the case of women, independence of the residuals, while in men, the residuals were autocorrelated.…”
mentioning
confidence: 99%
“…These findings present new research opportunities, as the power at VLF is related to changes in the humoral system 27 , while DFA fluctuations have been considered useful when analyzing the intrinsic behavior of a system 28 . Finally, the age of the participants influenced the final prediction model of VO 2max , with correlations of r = 0.423 in men and r = 0.212 in women, which has been considered in the development of other prediction models 29 . The Durbin Watson test for independence of variables showed, in the case of women, independence of the residuals, while in men, the residuals were autocorrelated.…”
mentioning
confidence: 99%
“…The results of this study indicated that the newly formulated regression equation, based on nonexercise variables of age, body mass, and resting heart Advances in Social Science, Education and Humanities Research, volume 574 rate, can significantly predict aerobic endurance (VO2max prediction) (Rexhepi & Brestovci, 2014). The current situation of Covid-19 pandemic makes it impossible to carry out activities involving many people.…”
Section: Resultsmentioning
confidence: 93%
“…The used formula for VO 2max in the others is based on age, body mass, and RHR. Nevertheless, it can be considered an appropriate estimation in case of missing exercise tests [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maximal aerobic capacity (VO 2max ) by spiroergometry was extracted if available. If not, it was estimated by the equation of Rexhepi and Brestoci [ 22 ]. Furthermore, data from sports performance tests with incremental exercise tests on running or cycle ergometer were considered: RHR, heart rates (HF), lactate, and power, respectively, and speed were extracted for analysis.…”
Section: Methodsmentioning
confidence: 99%